Uzņēmumu darbības īpatnības brīvajā ekonomiskajā zonā. - Gurtovaja, Viktorija (Latvijas Universitāte, 2014)
Bakalaura darba tēma ir „Uzņēmumu darbības īpatnības brīvajā ekonomiskajā zonā”. Bakalaura darba mērķis ir izpētīt un izvērtēt uzņēmumu darbību Rēzeknes speciālā ekonomiskā zonā (SEZā), to problēmas un nākotnes perspektīvas. Bakalaura darbs sastāv no teorētiskās, analītiskās un praktiskās daļas. Teorētiskajā daļā tiek aplūkota un noskaidrota uzņēmējdarbības būtība. Analītiskajā tiek analizēta Rēzeknes SEZ darbība. Praktiskajā daļā tiek analizēta uzņēmumu darbība Rēzeknes SEZā. Darba apjoms ir 62 lappuses, tajā iekļauti 20 attēli, 8 tabulas un 1 pielikums. Darbā izmantotās literatūras un avotu vienību skaits – 29. Atslēgas vārdi: uzņēmējdarbība, uzņēmējdarbības vide, Rēzeknes speciālā ekonomiskā zona, brīvās ekonomiskās zonas.

The Bachelor thesis is „Companies specificities of working in the free economics zone”. The goal Bachelor thesis is to explore and evaluate the company in Rezekne Special Economic Zone and Rezekne Special Economic Zone activities, the challenges and prospects for the future. Thesis consists of theoretical, analytical and practical parts. The theoretical part is discussed and clarified the nature of the business. Analytical analyses Rezekne Special Economic Zone activities. The practical part analyses activities of the company of the Rezekne Special Economic Zone. Bachelor’s thesis includes 62 pages, including 20 images, 8 tables and 1 appendix. Literature review consists of 29 sources. Keywords: business,the business environment, Rezekne Special Economic Zone, a free economic zone.
Companies specificities of working in the free economics zone.
Keywords: Vadībzinātne